ANGKRINGAN SEBAGAI RUANG PUBLIK DAN SARANA INTERAKSI SOSIAL DI KOTA BOGOR - Retno Dyah Kusumastuti; Airlangga Surya Kusuma (Jurnal Pustaka Komunikasi, 2022)
Angkringan currently acts as a public space in various cities, including in the city of Bogor. The advantages of angkringan, which offer cheap food and drinks, and give customers the freedom to socialize, make angkringan as an ideal public space for social interaction, especially for the lower middle class. The purpose of this study is to describe in detail how the role of angkringan as a public space and as a means of social interaction in the city of Bogor. The research method used for this study is descriptive qualitative with a case study approach. The data collection technique used in this study was observation and literature review method. This study shows that social interactions in angkringan happened in the form of social contact and interpersonal communication. The social contact in angkringan occured when angkringan customers learn and accept the norms that apply in angkringan, namely egalitarian norms and emphasis on face-to-face communication. The existence of these two norms enabled an effective and intese interpersonal communication. This made angkringan as a public space that can facilitate better social interaction for urban communities in Bogor City.